Parametry opadu deszczu wpływające na pojemność wodną korony drzew w warunkach kontrolowanych - Klamerus-Iwan, Anna (Leśne Prace Badawcze, 2014)
The subject of this research was the interception of precipitation, which is defined as the amount of water that can be retained by the entire surface of a tree. The aim was to measure the rate of interception under laboratory conditions in order to determine influential factors. To eliminate water absorption that would occur in living trees, we employed models of deciduous and coniferous trees enabling us to examine the effect of precipitation characteristics and the surface area individually. A sprinkler system that automatically recorded the amounts of water retained on the models was set up in the laboratory. Precipitation was simulated using 5 different intensities with 3 different raindrop sizes. Interception rates were affected by both, the intensity of the precipitation and raindrop size. The time required to reach maximum crown filling with water was variable and depended on plant surface parameters as well as simulated precipitation. The maximum water capacity of crowns was not a constant value even within one tree model, but changed depending on precipitation characteristics.